Primeiros doutorados em matemática no Brasil: uma análise histórica - Martines, Mônica de Cássia Siqueira [UNESP] (2014)
In this work we performed a historical analysis of the rst doctorates degrees in Mathematics in Brazil. The analysis starts with the understanding of the process that established the degree of Doctor of Mathematical Sciences in the mid nineteenth century in Brazil, in a process that includes the study of decrees and laws since the creation of the Royal Military Academy, in 1810, until that it has became into Military School, in 1839. We also studied the reforms on this Educational Institution, until that in 1842 the degree of Doctor was established by decree. We note that even after the institutionalization of that degree, it was only after the approval of its rules, published in 1846, which emerged the rst doctoral dissertations. We conducted a historical analysis of these essays and their authors, and presented here as a result of our research on the History of Mathematics in Brazil